Effects of Formulated Nano-Urea Hydroxyapatite Slow Release Fertilizer Composite on the Physical, Chemical Properties, Growth and Yield of Cyamopsis tetragonoloba (Cluster Beans) - Singam, Shylaja; Mesineni, Rao; Shilpa Chakra, Ch. (Asian Journal of Chemistry, 2020)
Urea and phosphorous fertilizers are commonly used in agriculture but, due to their solubility in water and transportation, cause eutrophication. Hence, it is thought worthwhile to investigate for urea hydroxyapatite nanoparticles which have less mobility and could supply required N and P macronutrients to the crops. These high surface area nanoparticles are synthesized through chemical co-precipitation method and it is assumed that due to their biocompatibility, act as rich phosphorous and nitrogen source. These are characterized by powder X-ray diffraction (PXRD), dynamic light scattering (DLS), scanning electron microscope (SEM), energy dispersive X-ray analysis (EDX) and Fourier transform infrared (FT-IR). The impact of urea hydroxyapatite nanofertilizer on growth and yield of cluster bean plants for the period of four months has been carried out. The experimental results have shown that the usage of these nanofertilizers have enhanced both the plant growth and yield. The application of urea hydroxyapatite nanocomposites for the bio-availability of plants considered to be environment friendly.